2014
DOI: 10.1039/c4ra07700h
|View full text |Cite|
|
Sign up to set email alerts
|

Towards applications in catalysis: investigation on photocatalytic activities of a derivative family of the Keplerate type molybdenum–oxide based polyoxometalates

Abstract: The photocatalytic potential of a derivative family of the Keplerate type nano-porous Mo-O based polyoxometalates with general formula [Mo 72 VI Mo 60 V O 372 (L) 30 (H 2 O) 72 ] nÀ (L ¼ CH 3 COO À , SO 4 2À ) (denoted Mo 132 ) has been evaluated by a prototype photocatalytic decoloration reaction of aqueous rhodamine B. The Mo 132 anions are found to be photocatalytically active centers, however they are unstable and subjected to decomposition in the solution form. The introduction of organic counter cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…While {Mo 72 Cr 30 } clusters were ineffective solar photocatalysts toward RhB degradation under both homogeneous (6%) and heterogeneous (0%) conditions, ammonium {Mo 132 } revealed a moderate efficiency of 48% under the homogeneous condition. Our finding showed that replacing the ammonium countercation by tetra- n -butylammonium, producing { n -Bu 4 N–Mo 132 } as an organic–inorganic hybrid material, promoted the decoloration rate to 60% . Nevertheless, protection of active sites by the long chains of the organic counterion dioctadecyldimethylammonium {DODA–Mo 132 } diminished its efficiency to 20% .…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…While {Mo 72 Cr 30 } clusters were ineffective solar photocatalysts toward RhB degradation under both homogeneous (6%) and heterogeneous (0%) conditions, ammonium {Mo 132 } revealed a moderate efficiency of 48% under the homogeneous condition. Our finding showed that replacing the ammonium countercation by tetra- n -butylammonium, producing { n -Bu 4 N–Mo 132 } as an organic–inorganic hybrid material, promoted the decoloration rate to 60% . Nevertheless, protection of active sites by the long chains of the organic counterion dioctadecyldimethylammonium {DODA–Mo 132 } diminished its efficiency to 20% .…”
Section: Resultsmentioning
confidence: 85%
“…Our finding showed that replacing the ammonium countercation by tetra-n-butylammonium, producing {n-Bu 4 N−Mo 132 } as an organic−inorganic hybrid material, promoted the decoloration rate to 60%. 31 Nevertheless, protection of active sites by the long chains of the organic counterion dioctadecyldimethylammonium {DODA−Mo 132 } diminished its efficiency to 20%. 18 The vanadium-containing Keplerate {Mo 72 V 30 } was inferior in the dye photodegradation, and a complicated exhibition was observed in RhB solution.…”
Section: Acs Applied Nano Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Figure S19, no significant change in the reaction rate was observed in the presence of methanol as an efficient OH radical scavenger, and O 2 was produced smoothly at the same rate observed in the absence of methanol. The absence of OH radicals in the reaction was also confirmed using terephthalic acid as a photoluminescent OH radical-trapping agent . Upon excitation at 315 nm, no change was observed in the PL intensity of the aqueous suspension (Figure S20), excluding the formation of any OH radical during the photodismutation reaction.…”
Section: Resultsmentioning
confidence: 65%
“…In recent years, POM clusters have received significant attention in photocatalytic degradation of organic pollutants. [14,15] It is necessary to explore new efficient POM-based photocatalysts. In addition, organometal (OM)-functionalized POMs provide a platform for the development of versatile inorganic-organic hybrid materials, [16][17][18][19][20] which may possess a preferable photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%